Reimagining prosperity : toward a new imaginary of law and political economy in the EU - Bartl, Marija (Cambridge studies in European law and policy., 2025)
The historic task of the European Union (EU) today, this book argues, is to articulate and institute a new imaginary of prosperity. Imaginaries of prosperity integrate societies around the shared pursuit of a prosperous future, rendering 'political-economic' questions as the main preoccupation of politics. The new imaginary of prosperity in the EU must be able to provide answers to contemporary societal challenges while also conjuring a world in which people want to live. Through analyses of several policy fields, the book shows that the EU has already made modest strides in fostering more caring consumption, circular products and technologies, sustainable industry, and fairer corporate activity. But the EU must go further and faster if it hopes to respond effectively to Europe's problems, while arresting another descent into tribalism. This title is also available as Open Access on Cambridge Core.